RNA-seq reveals differentially expressed genes between two indica inbred rice genotypes associated with drought-yield QTLs - Ereful, Nelzo C.; Liu, Li-Yu; Greenland, Andy; Powell, Wayne; Mackay, Ian; Leung, Hei (MDPI, 2020)
Two indica inbred rice lines, IR64, a drought-sensitive, and Apo, a moderately drought-tolerant genotype, were exposed to non- (control or unstressed) and water-stress treatments. Leaf samples collected at an early flowering stage were sequenced by RNA-seq. Reads generated were analyzed for differential expression (DE) implementing various models in baySeq to capture differences in genome-wide transcriptional response under contrasting water regimes. IR64, the drought-sensitive variety consistently exhibited a broader transcriptional response while Apo showed relatively modest transcriptional changes under water-stress conditions across all models implemented. Gene ontology (GO) and KEGG pathway analyses of genes revealed that IR64 showed enhancement of functions associated with signal transduction, protein binding and receptor activity. Apo uniquely showed significant enrichment of genes associated with an oxygen binding function and peroxisome pathway. In general, IR64 exhibited more extensive molecular re-programming, presumably, a highly energy-demanding route to deal with the abiotic stress. Several of these differentially expressed genes (DEGs) were found to co-localize with QTL marker regions previously identified to be associated with drought-yield response, thus, are the most promising candidate genes for further studies.